Our Experiences in Acute Arterial Embolism Treatment with Endovascular Techniques in Lower Extremity - Onur Saydam; Mehmet Atay (Genel Tıp Dergisi)
Objectives: The study aims to retrospectively evaluate the 1-year results of endovascular treatment with rheolytic thrombectomy(TR) or catheter-directed thrombolytic(CDT) infusion therapy in acute femoro-popliteal bypass graft occlusion. Methods: The patients who had a history of femoro-popliteal by-pass operation and during their follow-up diagnosed with ipsilateral acute limb ischemia between 2016 and 2018 were included. The total of 13 patients were included and they were divided into two groups according to their treatment methods (RT, n=8 vs CDT, n=5). Results: There was no statistically significant difference between the two groups in terms of demographic data and Rutherford embolism classification. Reolitic thrombectomy and catheter-directed thromolytic infusion primary patency values were 87.5% and 80% for 6 months, 75% and 60% for 12 months, respectively. Secondary patency values were found to be 100% in both groups for 6 months, and 87.5% and 80% for 12 months, respectively. There was no significant difference between the two groups in terms of primer and sekonder patency. Conclusion:Endovascular therapy can be preferred in the treatment of acute femoro-popliteal by-pass graft occlusion in selected patient groups due to its less invasiveness, early mobilization, and low mortality and morbidity rates compared to surgery,